2013
DOI: 10.3844/ajassp.2013.1140.1147
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality and Prevalence of Sick Building Syndrome Among Office Workers in Two Different Offices in Selangor

Abstract: This study was done to investigate the relationship between Indoor Air Quality (IAQ) and prevalence of Sick Building Syndrome (SBS) in two different offices (old and new) in Selangor. Hundred and seventy workers were selected consist of 85 office workers for each building. Questionnaire based on Indoor Air Quality and Work Symptoms Survey, NIOSH, Indoor Environmental Quality Survey, 1991 was used to record prevalence of SBS. Measurement of indoor air quality was performed using instruments recommended by IAQ C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 11 publications
2
39
0
Order By: Relevance
“…However, only a few office studies on SBS among office workers have been published from Malaysia. Zamani et al (2013) reported that one old office building had higher prevalence of SBS than a new office building. Prevalence of SBS was associated with carbon dioxide (CO 2 ), total VOC (TVOC), particulate matter 10 (PM10), particulate matter 2.5 (PM2.5) and ultrafine particles (UFP) levels in the offices (Zamani et al, 2013).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…However, only a few office studies on SBS among office workers have been published from Malaysia. Zamani et al (2013) reported that one old office building had higher prevalence of SBS than a new office building. Prevalence of SBS was associated with carbon dioxide (CO 2 ), total VOC (TVOC), particulate matter 10 (PM10), particulate matter 2.5 (PM2.5) and ultrafine particles (UFP) levels in the offices (Zamani et al, 2013).…”
mentioning
confidence: 97%
“…Zamani et al (2013) reported that one old office building had higher prevalence of SBS than a new office building. Prevalence of SBS was associated with carbon dioxide (CO 2 ), total VOC (TVOC), particulate matter 10 (PM10), particulate matter 2.5 (PM2.5) and ultrafine particles (UFP) levels in the offices (Zamani et al, 2013). Fadilah and Juliana (2012) found a higher prevalence of nasal symptoms in workers from new office buildings (Fadilah and Juliana, 2012).…”
mentioning
confidence: 97%
“…However, studies have shown that indoor environmental performances, including thermal and visual, have major impact on occupants' well-being (Salnikov and Karatayev, 2011;Bluyssen, 2010;Choi et al, 2012;Todorovic and Kim, 2012;Zamani et al, 2013). According to the Rio Declaration, the Principle 1 stated, "Human beings are at the center of concerns for sustainable development.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this concern, Klang Valley is continuously exposed to air pollution, which is approaching critical levels in a number of urban areas including Kuala Lumpur and Petaling Jaya (Musa et al, 2013). Thus, indoor environment in Malaysia is one of the particular interests to study where building-related illnesses still have not gained the same importance as those related to outdoor air quality (Shaharom, 2013). Furthermore, Malaysia is a tropical country, which has a lower ventilation rates, therefore enhancing the usage of open ventilation system in such buildings.…”
Section: Ajasmentioning
confidence: 99%